T cell repertoire to citrullinated self-peptides in healthy humans is not confined to the HLA-DR SE alleles; Targeting of citrullinated self-peptides presented by HLA-DP4 for tumour therapy. (4th May 2019) - Brentville, Victoria A; Symonds, Peter; Cook, Katherine W; Daniels, Ian; Pitt, Tracy; Gijon, Mohamed; Vaghela, Poonam; Xue, Wei; Shah, Sabaria; Metheringham, Rachael L; Durrant, Lindy G
ABSTRACT: Post-translational modifications are induced in stressed cells which cause them to be recognised by the system. One such modification is citrullination where the positive charged arginine is modified to a neutral citrulline. We demonstrate most healthy donors show an oligoclonal CD4 response in vitro to at least one citrullinated vimentin or enolase peptide. Unlike rheumatoid arthritis patients, these T cell responses were not restricted by HLA-DRB1 shared epitope (SE) alleles, suggesting they could be presented by other MHC class II alleles. As HLA-DP is less polymorphic than HLA-DR, we investigated whether the common allele, HLA-DP4 could present citrullinated epitopes. The modification of arginine to citrulline enhanced binding of the peptides to HLA-DP4 and induced high-frequency CD4 responses in HLA-DP4 transgenic mouse models. Our previous studies have shown that tumours present citrullinated peptides restricted through HLA-DR4 which are good targets for anti-tumour immunity. In this study, we show that citrullinated vimentin and enolase peptides also induced strong anti-tumour immunity (100% survival, p < 0.0001) against established B16 tumours and against the LLC/2 lung cancer model ( p = 0.034) both expressing HLA-DP4. Since most tumours do not constitutively express MHC class II molecules, models were engineered that expressed MHC class II under the control of an IFNγ inducible promoter. Immunisation with citrullinated peptides resulted in 90% survival ( p < 0.001) against established B16 HHD tumour expressing IFNγ inducible DP4. These studies show that citrullinated peptides can be presented by a range of MHC class II molecules, including for the first time HLA-DP4, and are strong targets for anti-tumour immunity.